Methodical approach to the information technology development for multidimensional assessment of the ethnic tension level in Autonomous Republic of Crimea - Богданович, Володимир Юрійович; Бальбек, Руслан Ісмаїлович (Ukrainian Scientific Journal of Information Security, 2014)
After the proclamation of Ukraine independence in the process of its nation-building of the state there was a row of new problems in the different spheres of life. There was a need for in creation of the model of the government control of public, political, economic, ethnic and other relations. One of the base principles of the state administration the complex social system there is providing of its social and political stability, the violation of that results in worsening of social life parameters of the population, significantly complicates handling of social and political processes. The main factors that destructively influence on providing of socio-political stability in AR Crimea and accordingly in the Ukraine, is an ethno-national tensions in the autonomy. The scientific research essentially of the ethnic factor in the public life potential ethnic of the Ukrainian creation of the state and problems of the politic and legal providing of development of the Ukrainian nation native people ethnic groups in Ukrainian society will allow to define the priorities for government in ethnic relations based on the rule of law as constituent management principle. However, the existing methodological apparatus evaluating the national ethnic tension is based on the methods of high-quality evaluation and does not allow getting it the quantitative estimations. In this article, the authors proposed the methodical approach to the development of information technology of multidimensional quantitative assessment of the level ethnic tensions in the interests providing of stability in AR Crimea. These results allow more targeted justify and implement national ethnic policy in AR Crimea and thereby ensure the social and political stability in the autonomy.